116 Serotonergic function in early Parkinson's disease with and without depression: a pilot study. Issue 3 (9th February 2012) - Newman, E; Khoo, T C; Patterson, J; Cavanagh, J; Pimlott, S; Grosset, K A; Grosset, D G
Abstract : Introduction: The role of the serotonergic system in Parkinson's disease (PD) depression is unclear. [123I] β-CIT, a single photon emission computed tomography (SPECT) radioligand, binds differentially to both dopamine and serotonin transporters (DAT, SERT). Aim: To assess the relationship between SERT activity and depressive symptoms in newly-diagnosed, antiparkinson drug-naïve PD patients with and without depression. Methods: Drug-naïve patients with a new clinical diagnosis of PD were assessed using the Unified Parkinson's Disease Rating Scale (UPDRS), Hamilton Depression Rating Scale (HAM-17), Montgomery-Asberg Depression Rating Scale (MADRS) and Hospital Anxiety and Depression Scale (HADS) and were imaged with [123I]β-CIT SPECT. Results: 10 patients (mean 59.0 (7.4) years) were recruited. Four patients were depressed (PD+D) and six were not (PD−D). No significant differences in DAT or SERT uptake were observed between PD+D and PD−D patients. No significant correlation was found between SERT uptake and depression scores. In PD-D patients significant positive correlation was found between SERT uptake and DAT uptake in multiple regions (midbrain SERT and right caudate DAT, r=0.968, p=0.001; midbrain SERT and right putamen DAT, r=0.953, p=0.003) but no such correlation was found in PD+D patients. Conclusion: There was no correlation between depressive symptoms and serotonergic function in newly diagnosed PD cases.